Impact of Dust and Sandstorms on 6G UAV Base Station Performance in Arid Saudi Arabian Environments - Shalaby A.M.; Othman N.S.; Shalaby M. (Institute of Electrical and Electronics Engineers Inc., 2025)
This research provides a detailed quantitative analysis of the challenges encountered in deploying 6G Unmanned Aerial Vehicle Base Stations UAV-BS in arid environments, specifically focusing on Saudi Arabia. The study meticulously quantifies the impact of dust and sand storms on these advanced communication systems, highlighting the substantial increase in signal attenuation and path loss under such conditions. Key findings include a marked dependency of transmitted power requirements on visibility at millimeter range high frequencies, (at 100 GHz). The results demonstrate that at this frequency, a decrease in ground visibility from 15 to 5 meters necessitates a significant increase in transmitted power by approximately 10 dB. Moreover, a striking 50 dB increase in path loss is observed when transitioning from a 3 GHz carrier frequency to 100 GHz under a ground visibility of 5 meters. This increase is attributed to a 30 dB rise in free space loss FSL due to the change in carrier frequency and an additional 20 dB attributed to increased dust attenuation at 100 GHz compared to 3 GHz. Our approach integrates PSO for dynamic UAV-BS positioning, effectively mitigating the adverse effects of dust and sand on signal quality. The research underscores the importance of considering UAV altitude, signal frequency, and ground visibility for optimal signal propagation. Additionally, it highlights the necessity of dynamic power management strategies within the network architecture to adapt to the unique challenges of arid environments. This study not only illuminates the practical implications for the deployment of UAV-BS in future 6G networks but also emphasizes the need for continuous adaptation of UAV-BS positioning in response to changes in visibility and that due to continuous change in the pattern of active users (asking for network services). The insights gained are crucial for ensuring reliable communication during environmental challenges, paving the way for more resilient and efficient wireless communication systems in demanding conditions. ? 2013 IEEE.